1985
DOI: 10.1139/z85-423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat quality on growth, age of first reproduction, and dispersal in Gunnison's prairie dogs (Cynomys gunnisoni)

Abstract: Populations of the highly social Gunnison's prairie dog (Cynomys gunnisoni) were studied at two sites in south central Colorado. The sites differed in availability of water, duration of the growing season, and the diversity and quantity of edible vegetation. At the lusher site, Quartz Creek, all age- and sex classes weighed significantly more than their counterparts at the more barren site, Blue Mesa. Growth rates and overwinter survival of Quartz Creek young were higher than at Blue Mesa. Two of 5 yearling fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 17 publications
0
38
1
Order By: Relevance
“…Social interactions among yellow-bellied marmots of areas with relatively short growing seasons are less agonistic and more friendly (ie socially tolerant) than those among marmots of areas with longer growing seasons (Barash 1973b(Barash , 1989. Similarly, Gunnison's prairie dogs reach sexual maturity more rapidly, and disperse at a younger age at sites with more extended growing seasons than prairie dogs of habitats with shorter growing seasons (Rayor 1985). Lastly, the rate of amicable interactions within groups (a measure of sociality) of Columbian ground squirrels Spermophilus columbianus decreases with the length of the plant (food) growing season (Ritchie and Belovsky 1990).…”
Section: The Parental Investment Hypothesismentioning
confidence: 99%
“…Social interactions among yellow-bellied marmots of areas with relatively short growing seasons are less agonistic and more friendly (ie socially tolerant) than those among marmots of areas with longer growing seasons (Barash 1973b(Barash , 1989. Similarly, Gunnison's prairie dogs reach sexual maturity more rapidly, and disperse at a younger age at sites with more extended growing seasons than prairie dogs of habitats with shorter growing seasons (Rayor 1985). Lastly, the rate of amicable interactions within groups (a measure of sociality) of Columbian ground squirrels Spermophilus columbianus decreases with the length of the plant (food) growing season (Ritchie and Belovsky 1990).…”
Section: The Parental Investment Hypothesismentioning
confidence: 99%
“…Yearlings of ground-dwelling sciurids do not reproduce, or reproduce at much lower rates, than older animals; examples include woodchucks (Snyder, 1962), Belding's ground squirrels Spermophilus beldingi (Sherman & Morton, 1984), Columbian ground squirrels (Festa-Bianchet, 1981;Dobson & Murie, 1987), Uinta ground squirrels Spermophilus armatus (Slade & Balph, 1974), thirteen-lined ground squirrels (McCarley, 1966), golden-mantled ground squirrels Spermophilus lateralis (Bronson, 1979), black-tailed prairie dogs (King, 1955;R. E. Smith, 1958;Hoogland, 1981Hoogland, , 1995), Gunnison's prairie dogs Cynomys gunnisoni (Rayor, 1985), Olympic marmots (Barash, 1973) and hoary marmots Marmota caligata (Barash, 1974a). Increased energy availability increased the frequency of reproduction in yearling black-tailed prairie dogs (Koford, 1958) and Gunnison's prairie dog yearlings bred only when food was more abundant (Rayor, 1985).…”
Section: Maternity Patterns and Comparisonsmentioning
confidence: 99%
“…E. Smith, 1958;Hoogland, 1981Hoogland, , 1995), Gunnison's prairie dogs Cynomys gunnisoni (Rayor, 1985), Olympic marmots (Barash, 1973) and hoary marmots Marmota caligata (Barash, 1974a). Increased energy availability increased the frequency of reproduction in yearling black-tailed prairie dogs (Koford, 1958) and Gunnison's prairie dog yearlings bred only when food was more abundant (Rayor, 1985). More yearling female Columbian ground squirrels reproduced on food-supplemented sites than on non-supplemented sites and in low-elevation habitats with a longer growing season (Dobson & Kjelgaard, 1985;Dobson, Zammuto & Murie, 1986;Dobson & Murie, 1987).…”
Section: Maternity Patterns and Comparisonsmentioning
confidence: 99%
“…Similarly, the hypothesis that adult aggression actively promotes dispersal by young male conspecifics was rejected in studies of M.flaviventris (Armitage 1973, Armitage and Downhower 1974, Downhower and Armitage 1981, Brody and Armitage 1985, and S. beecheyi (Dobson 1979). Rayor (1985) concluded that natal dispersal by male Cynomys gunnisoni resulted from direct conflict with other males. However, predictions for the conspecific aggression hypothesis were violated in studies of dispersal in Cynomys ludovicianus (Z. Halpin, personal communication) and S. columbianus (Festa-Bianchet and King 1984).…”
Section: ) S Armatus (Slade and Balph 1974) Or S Tereticaudus (Dumentioning
confidence: 99%
“…However, as in the present study, earlier workers have attempted to examine effects on sciurid dis-persal of several independent variables concurrently. Exploratory excursions often precede dispersal in young male S. beldingi (Holekamp 1 984a), Cynomys gunnisoni (Rayor 1985), Castor canadensis (Svendsen 1980), and Odocoileus hemionus (McCullough 1985). Similarly Dunford (1977) found no significant relationship between dispersal and population density, food availability, or aggression in S. tereticaudus.…”
Section: ] Pygathrix Nemaeus [Lippold 1977])mentioning
confidence: 99%